Oxygen regulation capacity in Discoglossus pictus tadpoles between moderate hyperoxia and acute hypoxia in water (Revista Española de Fisiología, 1988)
The oxygen dependence of aquatic oxygen consumption was measured in active and anesthetized stage XVIII Discoglossus pictus tadpoles (Amphibia, Anura).The active tadpoles are good oxygen regulators in moderate hyperoxia and moderate hypoxia, whereas they are oxygen conformers in acute hypoxia.Critical oxygen pressure was 52 mmHg O2.Anesthetizing the larvae changes them to perfect oxygen conformers between moderate hyperoxia and moderate hypoxia (249-063 mmHg O2).At stage XVIII the aquatic respiratory organs are still capable of producing oxygen regulation when free access to air is denied.The marked capacity for oxygen regulation in D.pictus tadpoles is concordant with the strong hypoxic environments in which these animals usually live in nature.